Designing volatile functionality in e-commerce web applications - Rossi, Gustavo Héctor (2006)
In this paper we present a flexible design approach and a software framework for integrating dynamic and volatile functionality in Web applications, particularly in e-commerce software. We first motivate our work with some examples. We briefly describe our base design platform (the OOHDM design framework). Next, we show how to deal with services that only apply to a particular set of application objects by clearly decoupling these services from the base conceptual and navigation design and by defining the concept of service affinity. We describe an implementation environment that seamlessly extends Apache Struts with the notion of services and service’s affinities. Finally, we compare our approach with others’ work and present some further research we are pursuing.